(untitled) (Revista Apotheke, 2024)
Interview conducted as part of the data collection for my Master’s research (PPGAV-UDESC) with the artist and businessman Diego Valdevino, from Impressionista Art Materials. During the interview, held virtually on July 16, 2024, through the Zoom platform, the questions were based on topics such as: production of handmade paints and the national market and composition of pigments, in addition to the production of a new professional gouache in the country.